DEVELOPMENT OF AR MEDIA FOR TURONGGO YAKSO DANCE TO IMPROVE ELEMENTARY SCHOOL STUDENTS UNDERSTANDING OF HUMAN MOTOR SYSTEM CONCEPTS - Novenntya Putri Prastiwi Nurrochma; Surayanah (Universitas Islam Negeri Mataram, 2025)
Teaching IPAS on the subject of the human musculoskeletal system in elementary schools still faces challenges in visualizing abstract joint concepts. The purpose of this study is to produce AR based learning media based on Turonggo Yakso dance that cain improve students conceptual uderstanding. This research was designed as a development study applying the ADDIE model, which includes the stages of needs analysis, product design, development, implementation, and evaluation. The analysis stage showed the need for interactive visual media to aid in understanding joint concepts. The design stage produced an AR media design that visualizes dance movements as a representation of the human musculoskeletal system. In the development stage, the media was declared highly valid and practical based on expert and user validation results. Implementation in sixth-grade students at SDN 1 Surodakan showed a significant difference between the pretest and posttest results based on the Wilcoxon Signed Rank Test (p ≤ 0.05). The evaluation stage showed an average N-Gain value of 0.83, which is in the high improvement category. Thus, the AR media for Turonggo Yakso Dance is declared effective in improving elementary school students' understanding of the human motion system concept.